IoT-enabled activity tracking collar for cats with GPS localization - Aripin, Siti Aisyah; Mohd Isa, Mohd Ali (College of Computing, Informatics, and Mathematics, 2025)
Pet tracking and health monitoring are a must to maintain pet safety and health, especially in those pets that like to stray and get lost. This project proposes an IoT-based smart collar that integrates GPS, WiFi, and various health sensors to provide real-time tracking of the location and health monitoring. The system consists of an ESP32- based collar equipped with Wi-Fi for indoor tracking, an MPU6050 accelerometer for activity tracking, and an MLX90614 infrared sensor for temperature monitoring. Data collected from the sensors is transmitted to Firebase, where it is processed and displayed through a mobile application, enabling pet owners to monitor their cat’s activity, health parameters, and location in real time. In addition, integration of Google Maps API for geolocation provides more accurate tracking, enables geofencing to alert owners in the event their pet gets out of a specified boundary, and enables the use of animal clinics nearby from one's location. The system offers an endto-end solution for pet owners with better monitoring, early response to any potential health issues, and better pet safety.